PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DALAM MENGAMBIL KREDIT PADA PT. BANK PERKREDITAN RAKYAT (BPR) BARELANG MANDIRI CABANG UTAMA PALM SPRING KOTA BATAM - Weki Lido Putra; Tibrani Tibrani; Yannik Ariyati (University of Riau Kepulauan, 2014)
This study aims to identify and analyze how big the impact of service quality on the level of satisfaction experienced by customers in taking Taking a Bank Loan at Bank Barelang Mandiri The Main Branch Palm Spring Batam City. The model used in this study is the method of observation, interviews, questionnaires, and literature study using Likert skla and sampling methods used are accidental by 86 respondents. The analytical method used is the method of multiple linear regression (multiple linear regression).From the research, the authors conclude that service quality consists of tangible (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) simultaneously have a positive influence on Customer Satisfaction. For partial test (t), not all variables have a positive and significant impact on customer satisfaction, with a significant level of 0.231 for tangible or 23.1%, reliability of -0.211 or 21.1%, responsiveness 0.383 or 38.3% , 0.762 or 76.2% assurance and empathy 0.409 or 40.9%.